RELATIONSHIP BETWEEN DEGREE OF OPTICAL NERVE DAMAGE ON LEVEL OF DEPRESSION AND ANXIETY PATIENT WITH PRIMARY GLAUCOMA: Oral Presentation - Observational Study - Resident - SETIAWAN, I KADEK AGUS; Rahayu, Ni Kompyang; Ariani, Ni Ketut Putri; Widiana, I Gde Raka; Kusumadjaja, I Made Agus; Juliari, I Gusti Ayu Made (Ophthalmologica Indonesiana, 2024)
Introduction & Objectives Glaucoma is one of the leading causes of irreversible global blindness and the second most common cause of blindness in the world after cataracts. Depression and anxiety often occur in glaucoma patients when glaucoma is first diagnosed, the effect of decreased vision function in glaucoma, side effects of glaucoma therapy both medically and surgically and financial effects due to length of treatment and loss of job due to limited vision. This study aims to determine the relationship of the degree of optic nerve damage to the level of depression and anxiety in patients with primary glaucoma. Methods This research is an analytic, prospective observational research with a cross-sectional study approach. The relationship between independent variables and dependent variables was analyzed. Results The Man Whitney test found a significant difference in anxiety scores between the severe and mild to moderate groups with a p value of 0.020 . The ANCOVA test found that there was a relationship between the degree of optic nerve damage in primary glaucoma and the level of anxiety after controlling for control variables. Conclusion This study can be concluded that there is a difference in the level of anxiety between the degree of severe and mild to moderate optic nerve damage. The level of anxiety itself corresponds to the degree of damage to the optic nerve. The more severe the damage to the optic nerve, increased of the patient’s anxiety score.